Hebrew myths : the book of Genesis. - Graves, Robert, 1895-1985; Patai, Raphael (RosettaBooks : Made available through hoopla, 2014)
This is a comprehensive look at the stories that make up the Old Testament and the Jewish religion, including the folk tales, apocryphal texts, midrashes, and other little-known documents that the Old Testament and the Torah do not include. In this exhaustive study, Robert graves provides a fascinating account of pre-Biblical texts that have been censored, suppressed, and hidden for centuries, and which now emerge to give us a clearer view of Hebrew myth and religion than ever. Venerable classicist and historian Robert Graves recounts the ancient Hebrew stories, both obscure and familiar, with a rich sense of storytelling, culture, and spirituality. This book is sure to be riveting to students of Jewish or Judeo-Christian history, culture, and religion.